Teacher Questioning in College English Class: A Guide to Critical Thinking (Global Journal of Human-Social Science, 2015)
Amidst the great revolution in China's education system, promoting critical thinking in school education to prepare students for the needs of modern world has been advocated by more and more educators. Critical thinking is a learned skill that needs to be cultivated by effective instruction. Research suggest that teacher questioning plays an important role in promoting students' critical thinking through classroom interaction. This article reviews literature on how critical thinking relates to teacher questioning instructional approach and advocates effective use of teacher questioning technique in college English class to actively engage students in the learning process and guide them to critical thinking.
Keywords: China; college English class; teacher questioning; critical thinking